Características sociodemográficas e fatores emocionais em idosas com e sem dor crônica - Donatti, Ariel (Universidade Federal de São Carlos, 2021)
The population aging process brings with it the phenomenon of the feminization of old age, that is, the prevalence of females among the elderly. Chronic pain and emotional factors such as hope, stress and depression affect the quality of life of a significant portion of elderly women, due to the social and cultural context together with biological and psychological issues, making them an important topic of study. Therefore, this study aimed to verify if there is an association between chronic pain, sociodemographic characteristics and emotional factors in community elderly women. This is a cross-sectional, descriptive study, based on the quantitative research method. A sample of elderly women aged 60 years or over registered in the areas covered by the Family Health Units in the city of São Carlos-SP (n=243) was analyzed. For data collection, the following were used: Elderly Characterization Sheet, Geriatric Depression Scale (GDS), Perceived Stress Scale (PSS), Herth Hope Scale (EEH) and Multidimensional Pain Assessment Scale (EMADOR). Comparative groups consisted of: (a) Group that presented chronic pain (n=151) and (b) Group that did not present chronic pain (n=92). The elderly women in the sample had a mean age of 68.94 years. There was a predominance of elderly women with little education, married, white, Catholic, practicing a religion, retired, with low income and considered insufficient to meet their needs and who did not have health insurance. The mean score of depressive symptoms in the group with chronic pain was 4.63 points (Md=4.00; SD = 3.05) and in the group without chronic pain it was 2.74 points (Md=2.00; SD = 2.18). The mean stress score in the group with chronic pain was higher – 21.07 points (Md=20.00; SD = 10.2) when compared to the group without chronic pain – 16.73 points (Md=16.00; SD = 8.60). The mean score of hope in the group with chronic pain was 40.33 points (Md=41.00; SD = 5.72) and in the group without chronic pain it was 42.36 points (Md=44.00; SD = 4 46). The difference in the means of the groups was statistically significant for all emotional variables (p<0.05). It is concluded that there is an association between chronic pain and emotional factors in elderly women in the community. The group of elderly women without chronic pain had less depressive symptoms, lower levels of stress and higher hope when compared to the group of elderly women with chronic pain. The results of this study indicate that the treatment of chronic pain should also include depressive and stress symptoms, as well as providing means for the person to have positive perspectives for the future and to improve their hope.
Sociodemographic characteristics and emotional factors in elderly women with and without chronic pain
Keywords: Dor crônica; Estresse psicológico; Depressão; Idoso; Saúde do idoso; Saúde da mulher; Qualidade de vida; Gerontologia; Geriatria; Chronic Pain; Psychological Stress; Depression; Elderly; Health of the elderly; Women's Health; Quality of life; Gerontology; Geriatrics; CIENCIAS DA SAUDE